Utilization of lemongrass (cymbopogon flexousus) essential oil as antimicrobial agent on pork cuts. - Bernal, Marlon Rey D.
This study addressed the rising demand for plant-based preservatives in response to health and consumer preferences along with the exposure of meat products in wet markets to an uncontrolled environment. Focusing on lemongrass essential oil (LEO) as a plant-based preservative for pork tenderloins, the study aimed to determine its antimicrobial efficacy and impact on sensory qualities after pan-frying. In a 4×4 factorial research design, the study investigated microbial loads at 0, 2, 4, and 6 hours, assessing three LEO concentrations (0.06, 0.16, 0.25) for their microbial inhibition. Microorganisms were enumerated using Total Plate Count (TPC). Simultaneously, a sensory evaluation involved 60 panelists to assess the acceptability of pan-fried pork with LEO treatments, followed by a preference test. The microbial load complied with FDA-Philippines standard at time 0 but exhibited an exponential increase after 2 hours, indicating accelerated growth over 6 hours. Application of LEO solutions effectively inhibited microorganisms on pork tenderloins, with higher LEO concentrations demonstrating increased inhibitory effects due to elevated phenolic compounds like citral. Results from the acceptability test revealed an inverse relationship between LEO concentration and its impact on taste, smell, and overall acceptability, suggesting that higher LEO amounts led to lower consumer acceptability, possibly due to it being overpowering. The preference test indicated a preference for the 0.06 LEO concentration, with 31 out of 60 panelists favoring the lowest concentration. In conclusion, this study contributes valuable insights into the efficacy of LEO as a preservative for pork tenderloins, addressing microbial growth and consumer acceptability. The preference for lower LEO concentrations underscores its potential as a viable alternative for microbial inhibition without compromising sensory qualities. Overall, the research contributes to the evolving knowledge of sustainable and meat preservation alternatives, presenting a promising avenue for reducing reliance on synthetic preservatives in the food industry.